Size-controlled starch nanoparticles prepared by self-assembly with different green surfactant: The effect of electrostatic repulsion or steric hindrance. (15th May 2016) - Li, Xiaojing; Qin, Yang; Liu, Chengzhen; Jiang, Suisui; Xiong, Liu; Sun, Qingjie
Highlights: Size-controlled starch nanoparticles by self-assembly were prepared. The control effect of surfactants during the fabrication of starch nanoparticles was studied. Starch types significantly influenced the characteristic of starch nanoparticles. The ultrafine nanoparticles were obtained with the addition of surfactants. The thermal stability of nanoparticles with surfactants was improved. Abstract: To study the control effect of surfactants in the process of formation of starch nanoparticles by self-assembly, different surfactants (sodium dodecyl sulfate (SDS), polysorbate 80 (Tween 80), and sorbitan monooleate (Span 80) were added during the fabrication of waxy corn starch nanoparticles (WCSNPs) and potato starch nanoparticles (PSNPs), and their characteristics were determined and compared. The results showed that WCSNPs with SDS and Tween 80 had smaller particle size (28–35 nm and 15–24 nm, respectively) than that of WCSNPs (50–120 nm). The surfactants significantly increased the dispersion and thermal stability of nanoparticles. Short-chain amylose debranched from waxy corn starch had a lower degree of polymerization than that debranched from potato starch and were easier to retrograde, resulting in higher gelatinization enthalpy of WCSNPs. However, PSNPs were smaller in size and achieved better stability than WCSNPs due to stronger electrostatic repulsion caused by a higher absolute value of zeta potential.